The Accuracy Of Ultrasonography And CT Scans In Diagnosing Liver Tumours - Salima Baqir Alsaadi; Saad Abdul Kareem Mohammed; Ali I. Omran Al-Saadawi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Both benign and malignant liver tumours may occur. Multiple nodules or a single mass might be diffusely invasive. Our research diagnosed patients using CT scans and ultrasounds. We compared these strategies to determine which is better. A precise biopsy was performed on each tissue liver tumour to confirm the diagnosis of liver tumour. A 40 liver tumour patients were participated in this study included 24 men and 16 women. The average patient age was 52. The biopsy results were compared to CT and ultrasonography data for each subject. Ultrasonography resulted in 23 (57.5%) patients with malignant tumours and 9 (22.5) benign tumours, of which 8 (20%) were healthy. On the other hand, the CT scan results showed that 23 individuals (57.5%) had malignant tumours, and 17 (42.5%) had benign ones. These data suggest that CT scans are 100% more efficient than ultrasonography in identifying liver tumours.